The Role of Scintigraphy and Hybrid Single-Photon Emission Tomography in Comparison with Laboratory Data in a Comprehensive Examination of Patients with Secondary Hyperparathyroidism - V. Е. Prokina; А. А. Ansheles; A. V. Tarasov; A. S. Ametov; V. B. Sergienko (Вестник рентгенологии и радиологии, 2022)
Objective: to estimate the possibilities and determine the diagnostic value of scintigraphy and single-photon emission computed tomography combined with computed tomography (SPECT/CT) in the assessment of the functional state of parathyroids in comparison with laboratory data in patients with secondary hyperparathyroidism (SHPT).   Material and methods. The study consistently included 64 patients with the established diagnosis of SHPT due to the acquired vitamin D deficiency or with terminal chronic kidney disease (CKD), with the presence of ultrasound data and laboratory tests of calcium-phosphoric exchange indicators. Neck and mediastum nuclear study with 99mTc-methoxy-isobutyl-isonitrile (MIBI) was performed in the planar two-phase scintigraphy mode according to the standard protocol with an estimation of parathyroid visualization intensity, as well as in SPECT/CT performed 1 hour after MIBI injection.   Results. In the group of patients with CKD as a cause of SHPT (n = 14), the most pronounced increase of parathyroid hormone (PTH) level (210.8 ± 103.0 vs. 107.0 ± 40.2 pg/ml in patients with vitamin D deficiency (n = 50, p < 0.001)) and phosphorus (mean 1.39 ± 0.51 mmol/l), as well as excess of normal levels of alkaline phosphatase (407.7 ± 338.1 units/l) were noted. In patients with vitamin D deficiency, impaired parathyroids according to SPECT/CT data was visualized in 8 % of cases, and in patients with CKD in 14.3 %. No significant differences in the mean levels of vitamin D in patients with (n = 46) and without (n = 4) modified parathyroids according to scintigraphy were detected: 26.06 ± 13.19 vs. 25.82 ± 18.80 ng/ml, respectively (p = 0.97). Differences in PTH and calcium levels were not observed: 91.3 ± 39.2 vs. 89.2 ± 29.5 pg/ml (p = 0.90), 2.53 ± 0.21 vs. 2.58 ± 0,15 mmol/l (p = 0.64), respectively.   Conclusion. The neck SPECT/CT is a key method of topical imaging of impaired parathyroids in preoperative preparation of patients with SHPT caused by CKD. The method may have a diagnostic value in treatment-resistant patients with vitamin D deficiency and upper-normal PTH and calcium levels in terms of detection of the nodular form of parathyroid hyperplasia. The implementation of SPECT/CT after 1 hour after MIBI injection increases the sensitivity of the study.